Acoustical and volumetric investigation of polyethylene glycol 400 and polyethylene glycol 4000 in aqueous solutions of glycerol at different temperatures. (December 2018) - Kaur, Kirandeep; Juglan, K.C.; Kumar, Harsh
Highlights: The volumetric and ultrasonic studies of polyethylene glycol 400 and polyethylene glycol 4000 in aqueous medium have been examined at different temperature. The thermodynamic properties such as density and speed of sound estimations divulge information about the interactions which may exist in the mixtures. The extent of interaction intensifies with respect to concentration of glycerol solution as well as with molecular mass of PEGs; which means that solute-solvent interactions strengthen from PEG-400 to PEG-4000. The apparent molar volumes of transfer upsurge with surge in concentration of glycerol. The pair-wise interactions have been anticipated from pair and triplet interaction coefficients. Abstract: The intermolecular interactions of glycerol with two polyethylene glycols i.e. polyethylene glycol 400 and polyethylene glycol 4000 in aqueous medium have been examined from the measurements of density and ultrasonic speed at temperatures T  = (293.15, 298.15, 303.15, 308.15) K and experimental pressure p  = 0.1 MPa. The apparent molar volume ( V ϕ ), partial molar volume ( V ϕ o ) and partial molar volume of transfer ( Δ V ϕ o ) have been evaluated from density data for polyethylene glycols from water to aqueous glycerol solutions. The limiting apparent molar expansibilities have also been evaluated. The ultrasonic speed measurements are used to determine apparent molar isentropic compression ( K ϕ, s ), partial molar isentropic compression ( K ϕ, s o ) and partial molar isentropic compression of transfer ( Δ K ϕ, s o ) for polyethylene glycols from water to aqueous glycerol solutions. From (partial molar volume and partial molar isentropic compression) of transfer, the pair and triplet coefficients are calculated. By the perusal of these determined parameters, the results have been explicated based upon the competing patterns of physicochemical interactions of co-solutes and the solvents.